Chapter LaCoast Atlas: a consistent database to support sustainable coastal zone management - Bosi, Filippo (Proceedings e report, 2020)
The paper illustrates the LaCoast Project (LAnd cover changes in COASTal zones), a harmonised and consistent geo-referenced database that constitute a base tool for integrated spatial analysis of policies. It is meant to support sustainable management of the coastal areas trough the collection of information about their state and the impact of anthropic activities on them. The aim of the project ad its tools is assisting the development of tailored European policies for coastal zone management to be used both at regional and national level